‘Compañerismo’: Care and Power in Affective Labor Relations - Fernandez-Ossandon, R (SAGE Publications Ltd, 2023)
Many Chilean women employers desire domestic workers who are also ‘partners’ or ‘someone to do life with’. Taking ‘partnership’ or ‘compañerismo’ seriously, this paper draws on an affective labor framework and economic sociology to examine how care and power operate in affective and highly commodified labor relations between Chilean women employers and migrant Filipina domestic workers. We contextualize this discussion within historical relations of servitude in Chile and salient demands for more horizontal social and gender relations. We show that rather than reinforcing power or control, employers’ emphases on affective aspects of the labor relation enable their willful ignorance of power hierarchies, through normalizing the racialized presence of the worker in the household. However, explicit talk about money exposes the material conditions of affect and care in this racialized affective relationship. This reveals the uneven distribution and production of both care and power in the household, and highlights the disruptive nature of care work as affective labor. © The Author(s) 2022.